2022
DOI: 10.3390/children9050599
|View full text |Cite
|
Sign up to set email alerts
|

Peer Status as a Potential Risk or Protective Factor: A Latent Profile Analysis on Peer Status and Its Association with Internalizing Symptoms in Adolescents with and without Parental Physical Abuse Experience

Abstract: Research has well established that parental physical abuse experiences can lead to devastating consequences for adolescents, with peer relationships acting as both protective and risk factors. With the person-centered latent profile analysis (LPA), we analyzed questionnaire data from a cross-sectional study in 2020 composed of a sample of 1959 seventh-grade high school students from Switzerland. This study investigated and compared peer-status profiles combining peer acceptance and peer popularity for adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 121 publications
1
18
0
2
Order By: Relevance
“…To protect adolescents from the consequences of IPV exposure, the present article addresses several issues: First, the prevalence of IPV exposure should be researched more thoroughly, and society should be sensitized to the strong consequences of IPV exposure. As a further step, prevention efforts in schools should focus on promoting self-esteem, self-efficacy, and social skills, because they significantly increase the chances of being in the resilient class, and they can also be promoted in the school system [100].…”
Section: Discussionmentioning
confidence: 99%
“…To protect adolescents from the consequences of IPV exposure, the present article addresses several issues: First, the prevalence of IPV exposure should be researched more thoroughly, and society should be sensitized to the strong consequences of IPV exposure. As a further step, prevention efforts in schools should focus on promoting self-esteem, self-efficacy, and social skills, because they significantly increase the chances of being in the resilient class, and they can also be promoted in the school system [100].…”
Section: Discussionmentioning
confidence: 99%
“…Defining the criteria for resilience can pose a challenge because it encompasses multiple indicators, which must be selected according to a specific adversity, a domain (such as school) and a developmental phase ( 29 ). As studies with the first two survey-waves of our project have shown ( 30 , 31 ), family violence experiences may lead not only to neurodevelopmental disorders such as depression and dissociation, but also to significantly higher cortisol levels ( 25 , 32 , 33 ), which can impair adolescents’ personal, social, and academic development ( 31 ). Based on our previous work on resilience pathways in adolescence despite family physical abuse ( 15 ), we expanded the data scope to four survey waves of data over three years and specifically related resilience pathways to HPA levels.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue features 18 articles that examine family risk and resilience among children and adolescents across developmental stages, ranging from early childhood to late adolescence/young adulthood. A wide range of child outcomes are examined in these studies, including children’s use of electronic devices [ 1 , 2 ], maltreatment experiences [ 3 ], mental health [ 4 , 5 , 6 , 7 ], school readiness and academic functioning [ 8 ], suicidal thoughts and behaviors [ 9 ], socioemotional development [ 10 , 11 , 12 , 13 ], and resilient/adaptive functioning [ 14 , 15 , 16 ].…”
mentioning
confidence: 99%
“…Focusing on child physical abuse as a risk factor, Favre et al identified distinct profiles of peer status among adolescents with and without physical abuse experiences. They found that higher levels of dissociation predicted membership in the rejected–unpopular group for adolescents with physical abuse experiences [ 13 ]. Interestingly, many unique family risk factors were found in studies that focused on problematic electronic use by children.…”
mentioning
confidence: 99%
See 1 more Smart Citation